Legal regulations to ensure the satisfaction of living organ donors - Sarah, Mohammad Ali Jehad (Journal of Economic, Administrative and Legal Sciences, 2025)
This research addresses the issue of consent in organ donation among living individuals, highlighting the legal frameworks governing donation from the perspective of Jordanian law. This research aims to clarify and define the legal framework that ensures the donor’s consent for organ donation is free and explicit, without any external pressures or influences, and in accordance with the principles of the Jordanian Civil Code and ethical and social values. The researcher used the analytical method in this study when examining the legal texts contained in the Law on the Use of Human Body Organs and the Jordanian Civil Code, with the aim of understanding and interpreting the laws related to the donor’s consent and its regulations. The researcher concluded the study with several findings and recommendations, the most notable of which was that the Human Body Parts Utilization Law did not explicitly state the obligation to inform the donor of all potential health and psychological risks resulting from the donation, nor did it stipulate the donor’s right to withdraw from the donation before the procedure. The researcher proposed to the Jordanian legislator the necessity of explicitly stating the obligation to inform the donor and their right to withdraw from the donation before the procedure is completed.